2021
DOI: 10.1128/jvi.02214-20
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Use of Galectin-9 and Blockade of the TIM-3 Receptor in the Latent Cellular Reservoir of HIV-1

Abstract: Reactivation of latent HIV-1 is a necessary step for the purging of the viral reservoir, although it does not seem to be enough. The stimulation of HIV-1 specific cytotoxic T lymphocytes (CTL) may be just as essential for this purpose. In this study, we aimed to show the effect of galectin-9 (Gal-9), known to revert HIV-1 latency, in combination with the blockade of TIM-3, a natural receptor for Gal-9 and an exhaustion marker. We confirmed the ability of Gal-9 to reactivate latent HIV-1 in Jurkat-LAT-GFP cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“… 99 Furthermore a recent report demonstrated the ability of Gal-9 to reactivate latent HIV-1 in a jurkat T-cell line. 52 This finding is consistent with a recent study showing Gal-9 shedding by neutrophils can activate T cells via binding to CD44 which leads to T cell activation in PWH. 100 CD155 is a ligand of the TIM-3 receptor and was shown to be upregulated on CD4+ Tfh cells that reside in the lymph node, a major site of HIV persistence.…”
Section: Tim-3supporting
confidence: 93%
See 1 more Smart Citation
“… 99 Furthermore a recent report demonstrated the ability of Gal-9 to reactivate latent HIV-1 in a jurkat T-cell line. 52 This finding is consistent with a recent study showing Gal-9 shedding by neutrophils can activate T cells via binding to CD44 which leads to T cell activation in PWH. 100 CD155 is a ligand of the TIM-3 receptor and was shown to be upregulated on CD4+ Tfh cells that reside in the lymph node, a major site of HIV persistence.…”
Section: Tim-3supporting
confidence: 93%
“…In some individuals, this could be reduced upon ART and blocking TIM-3 interaction resulted in reinvigoration and restoration of CD8 effector functions ex vivo 49 implying that neutralizing TIM-3 may have a role in approaches to eliminate the HIV reservoir. 52 …”
Section: Tim-3mentioning
confidence: 99%
“…When Tim-3 on NK cells bind to its ligands, its function of secreting cytokines and killing target cells is diminished (20)(21)(22). It has been assumed that the Tim-3-Galectin-9 pathway plays an important role in regulating tumor cells escaping from immune surveillance (23,24). In our study, of all the Tim-3 ligands, only CEACAM1 was expressed on NK-92 cells (about 70%).…”
Section: Nk Cells Are An Important Part Of Innate Immunity and Can Di...mentioning
confidence: 55%
“…Specifically, Tim-3 can interact with Gal-9 via the N-terminal IgV domain, which can trigger apoptosis in T helper type 1 immune cells ( 20 , 21 , 27 ). A recent report demonstrated that blocking Tim-3 could enhance the response of cytotoxic T lymphocytes to purge the latent reservoir in Gal-9-treated CD4 + T cells, implying that neutralizing Tim-3 may be an effective approach to eliminate the virus reservoir ( 75 ). Further studies will define how Nef inhibitors can be used to block Tim-3 upregulation to potentially aid in elimination of the viral reservoir.…”
Section: Discussionmentioning
confidence: 99%